International Finance and Financial Crises : Essays in Honor of Robert P. Flood Jr. (Washington, D.C. : International Monetary Fund, 2000)
This book contains the proceedings of a conference held in honor of Robert P. Flood Jr. Contributors to the conference were invited to address many of the topics that Robert Flood has explored including regime switching, speculative attacks, bubbles, stock market voloatility, macro models with nominal rigidities, dual exchange rates, target zones, and rules versus discretion in monetary policy. The results, contained in this volume, include five papers on topics in international finance.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet